2004
DOI: 10.1093/chemse/bjh010
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Sensitivity for Carboxylic Acids in Spider Monkeys and Pigtail Macaques

Abstract: Using a conditioning paradigm, the olfactory sensitivity of four spider monkeys and four pigtail macaques for a homologous series of carboxylic acids (n-propionic acid to n-heptanoic acid) was investigated. With only few exceptions, the animals of both species significantly discriminated concentrations <1 p.p.m. from the odorless solvent and in several cases individual monkeys even demonstrated thresholds <1 p.p.b. The results showed (i). both primate species to have a well-developed olfactory sensitivity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
17
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
8
17
1
Order By: Relevance
“…It is interesting to note, however, that the detection threshold for geraniol (Schmidt,'82), a monoterpenoid known to act as a pheromone in mice (Kayali-Sayadi et al, 2003), is in the same range as that found for 2,5-DMP which has also been demonstrated to be a pheromone in this species (Daev et al, 2007), suggesting that the behavioral relevance of odorants might affect a species' olfactory sensitivity. This supposition is supported by our finding that in the spider monkeys the olfactory detection thresholds for the alkylpyrazines tested here generally do not rank among the lowest reported so far in this species Laska et al, 2004Laska et al, , 2005bJoshi et al, 2006;Laska et al, 2006aLaska et al, ,c,d, 2007. Further support for the notion that the behavioral relevance of odorants rather than genetic or neuroanatomical properties may affect a species' olfactory sensitivity comes from the fact that spider monkeys do not generally perform poorer on olfactory detection tasks compared with mice but clearly outperform the latter in terms of detection thresholds for pentyl acetate, an ester found in the odor of various fruits consumed by A. geoffroyi (Yee and Wysocki, 2001;Hernandez Salazar et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is interesting to note, however, that the detection threshold for geraniol (Schmidt,'82), a monoterpenoid known to act as a pheromone in mice (Kayali-Sayadi et al, 2003), is in the same range as that found for 2,5-DMP which has also been demonstrated to be a pheromone in this species (Daev et al, 2007), suggesting that the behavioral relevance of odorants might affect a species' olfactory sensitivity. This supposition is supported by our finding that in the spider monkeys the olfactory detection thresholds for the alkylpyrazines tested here generally do not rank among the lowest reported so far in this species Laska et al, 2004Laska et al, , 2005bJoshi et al, 2006;Laska et al, 2006aLaska et al, ,c,d, 2007. Further support for the notion that the behavioral relevance of odorants rather than genetic or neuroanatomical properties may affect a species' olfactory sensitivity comes from the fact that spider monkeys do not generally perform poorer on olfactory detection tasks compared with mice but clearly outperform the latter in terms of detection thresholds for pentyl acetate, an ester found in the odor of various fruits consumed by A. geoffroyi (Yee and Wysocki, 2001;Hernandez Salazar et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Exactly the same correlation can be found in human subjects when using the threshold values as depicted in Figure 4 (Spearman, r s 5 0.56, P 5 0.0045). Several studies in various species found that detection thresholds vary systematically among members of homologous series of aliphatic odorants, which represent the most simple case of adding alkyl groups to the end of a straight and unbranched carbon backbone (Hernandez Laska et al, 2004Laska et al, , 2006bLaska et al, ,c, 2007. However, to the best of our knowledge no other study in any species so far assessed whether the addition of increasing numbers of alkyl or other functional groups to a non-aliphatic carbon backbone systematically affects detectability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemosensory abilities in primates appear to vary in relation to numerous ecological niches inhabited by different species, which may in turn influence dietary and communicatory specializations (Barton et al, 1995;Laska et al, 2000Laska et al, , 2004. Accordingly, anatomical systems specialized to detect chemical signals exhibit variations among primate taxa.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the sensory structures of the olfactory system and visual system may scale quite differently to the rest of the brain, and these evolutionary trends have been related to ecological variables (Frahm, 1985;Barton et al, 1995). In contrast to these studies, some comparative studies have explicitly debated whether olfactory capabilities differ between primates and other mammals, or between haplorhine and strepsirrhine primates (Cave, 1973;Laska et al, 2000Laska et al, , 2004.…”
mentioning
confidence: 99%